Overallotment option restrictions and contract choice in initial public offerings - Dunbar, Craig G. (Journal of Corporate Finance, 1997)
Relaxation of the national association of securities dealers (NASD) limit on overallotment option use in 1983 provides a natural experiment to test the substitutability or complementarity of underwriting contract terms in initial public offerings. For firms that would find the initial limit constraining, use of terms that are substitutes (complements) should decrease (increase) after the limit is raised. The evidence indicates that warrant compensation and overallotment options are substitutes. Underwriter reputation and overallotment options are substitutes if warrants are used as compensation and complements otherwise. The significant change in contract terms after 1983 suggests the initial NASD policy was costly.